Introduction to research in the health sciences - Polgar, Stephen; Thomas, Shane A. (Edinburgh Elsevier, 2020)
Now in its 7th edition this textbook is a must have for any health professional student. It provides a comprehensive overview of health research, in a concise and easy to read format using examples directly related to the health sciences. It helps students understand health research models, and how research goes on to inform and improve evidence-based clinical practice. For practitioners it provides guidance on published research in journals, providing an essential tool to keep their practice evidence based. Uses simple language and demystifies research jargon Covers both quantitative and qualitative research methodology, taking a very practical approach Provides an extensive glossary for better understanding of the language of research Fully updated online interactive self-assessment tests including MCQs, true or false questions and short answer questions.
Machine generated contents note: SECTION I Methodological Foundations of Health Research -- 1. Foundations of Health Research -- 2. Quantitative and Qualitative Methods -- 3. Research Process -- SECTION II Research Planning -- 4. Formulation of Research Questions -- 5. Sampling Methods and External Validity -- 6. Ethics -- SECTION III Research Designs -- 7. Experimental Designs and Randomized Controlled Trials -- 8. Surveys and Quasi-Experimental Designs -- 9. Qualitative Research -- SECTION IV Data Collection -- 10. Questionnaires and Survey Design -- 11. Mixed Methods -- 12. Interviewing Techniques -- 13. Measurement and Observation -- SECTION V Descriptive Statistics -- 14. Organization and Presentation of Data -- 15. Measures of Central Tendency and Variability -- 16. Standard Scores and Normal Distributions -- 17. Correlation -- SECTION VI Data Analysis and Inference -- 18. Probability and Confidence Intervals -- 19. Hypothesis Testing -- 20. Effect Size and the Interpretation of Evidence -- 21. Qualitative Data Analysis -- 22. Critical Evaluation of Published Research -- SECTION VII Evaluation and Dissemination of Research Results -- 23. Synthesis of Research Evidence: Systematic Reviews and Meta-Analyses -- 24. Translational Research.
Previous edition: Edinburgh: Churchill Livingstone, 2013.
Includes bibliographical references and index.
Keywords: Medicine -- Research; Biomedical Research -- methods; Research Design